2021
DOI: 10.1007/s13300-021-01067-1
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Regional Subanalysis of a Real-World Study in Patients with Type 2 Diabetes Treated with Gliclazide MR During Fasting: DIA-RAMADAN

Abstract: Introduction: To analyse the safety and effectiveness of gliclazide modified release (MR) in adults with type 2 diabetes mellitus participating in Ramadan from three geographically and culturally different regions of the world included in the DIA-RAMADAN study. Methods: DIA-RAMADAN was a real-world, observational, international, non-comparative study. The global study population was divided into three regional subgroups, with data gathered at inclusion 6-8 weeks prior to Ramadan (V0), during Ramadan (4.5 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Four reports in 2021 addressed the antidiabetic pharmacological therapies during Ramadan. Two were related to the DIA-Ramadan study, 15,16 and the other two were systematic reviews and metanalysis. 17,18 Raza et al 15 assessed the safety and effectiveness of gliclazide modified release (MR) of 60 mg in people with controlled or suboptimal-controlled T2DM.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Four reports in 2021 addressed the antidiabetic pharmacological therapies during Ramadan. Two were related to the DIA-Ramadan study, 15,16 and the other two were systematic reviews and metanalysis. 17,18 Raza et al 15 assessed the safety and effectiveness of gliclazide modified release (MR) of 60 mg in people with controlled or suboptimal-controlled T2DM.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Thirteen adverse events unrelated to gliclazide MR were reported during the study period. Also, Hassanein et al 16 reported another subgroup analysis from the same study (DIA-RAM-ADAN) by considering three geographically and culturally different regions. Data were captured at inclusion 6 to 8 weeks prior to Ramadan, during Ramadan (4.5 weeks), and 4 to 6 weeks after Ramadan.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients receiving gliclazide MR with a baseline BMI of ≥ 25 kg/m 2 lost 0.9–2.2 kg in the EASYDia study [ 65 ]. In the DIA RAMADAN study, the average weight loss in the overall study population was 0.5 kg [ 43 ], but was highest (0.7 kg) in patients residing in the Middle East [ 66 ]. In the ADVANCE trial, an average gain of only 0.1 kg was reported after 5 years of intensive glucose control with gliclazide MR [ 45 ].…”
Section: Establishing Early Glycaemic Control In Patients With Diabetesmentioning
confidence: 99%
“…The current prevalence of DM in countries such as Bahrain, Saudi Arabia, Kuwait, Oman, Qatar, and United Arab Emirates (UAE) ranges from 8 to 27% [2][3][4][5]. At this moment, there are more than 1 billion Muslims around the world, mainly located in the Asia-Pacific region, Sub-Saharan Africa, and the Middle East/North Africa [6,7]. However, the number of patients with DM, particularly type 2 DM (T2DM), is expected to increase dramatically in the coming years.…”
Section: Introductionmentioning
confidence: 99%